Resource management of marriage expenditure among Malay Muslim from Islamic perspective - Syh Noorul Madihah Syed Husin; Tengku Fatimah Muliana Tengku Muda; Zurita Mohd Yusoff; Siti Khatijah Ismail; Normadiah Daud (Penerbit Universiti Kebangsaan Malaysia, 2024)
Wedding ceremonies at present are increasingly celebrated on a large scale with various forms of receptions and meticulous preparations from the organisers. The cost required to organise various traditional wedding customs coupled with the current celebration trend seems to be increasing over time. As a result, young people who wish to hold a wedding ceremony can no longer be frugal on the provision of resources to manage wedding expenditures. Without proper management of wedding expenses, various risks related to failure in personal financial management may incur. Thus, this qualitative research is conducted to analyse the management patterns of wedding expenditures from the perspective of Islamic law. Data were collected through interviews with 20 married informants from Peninsular Malaysia. This research found that the main sources of expenditure used by the informants were from their respective savings. The study shows that the management of the informants’ wedding expenses is still in line with Islamic law. However, it is suggested that there should be specific guidelines in helping the community, especially young people who will set up a household, to manage their wedding expenses, particularly in matters relating to the sources of expenditure.